COVID-19 : insights and prospects from shifting learning experiences in Stellenbosch University’s postgraduate diploma in sustainable development - Van den Bergh, Camryn (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPhil)--Stellenbosch University, 2023.